Moderate, but not excessive, training attenuates autophagy machinery in metabolic tissues - da Rocha, Alisson L.; Pinto, Ana P.; Morais, Gustavo P.; Marafon, Bruno B.; Rovina, Rafael L.; Veras, Allice S. C. [UNESP]; Teixeira, Giovana R. [UNESP]; Pauli, José R.; de Moura, Leandro P.; Cintra, Dennys E.; Ropelle, Eduardo R.; Rivas, Donato A.; et al. (MDPI, 2020)
The protective effects of chronic moderate exercise-mediated autophagy include the prevention and treatment of several diseases and the extension of lifespan. In addition, physical exercise may impair cellular structures, requiring the action of the autophagy mechanism for clearance and renovation of damaged cellular components. For the first time, we investigated the adaptations on basal autophagy flux in vivo in mice’s liver, heart, and skeletal muscle tissues submitted to four different chronic exercise models: endurance, resistance, concurrent, and overtraining. Measuring the autophagy flux in vivo is crucial to access the functionality of the autophagy pathway since changes in this pathway can occur in more than five steps. Moreover, the responses of metabolic, performance, and functional parameters, as well as genes and proteins related to the autophagy pathway, were addressed. In summary, the regular exercise models exhibited normal/enhanced adaptations with reduced autophagy-related proteins in all tissues. On the other hand, the overtrained group presented higher expression of Sqstm1 and Bnip3 with negative morphological and physical performance adaptations for the liver and heart, respectively. The groups showed different adaptions in autophagy flux in skeletal muscle, suggesting the activation or inhibition of basal autophagy may not always be related to improvement or impairment of performance.
Keywords: Autophagy; Colchicine; Concurrent training; Endurance training; Exercise; Overtraining; Resistance training